Mineral Concentrations in Grazed Cool-Season Annual Grass Pastures in North Florida - Bob Myer; G. Chelliah; Lee McDowell; Nancy Wilkinson; Ann Blount; Cheryl Mackowiak (EDIS)
AN224, a 3-page illustrated fact sheet by Bob Myer, G. Chelliah, Lee McDowell, Nancy Wilkinson, Ann Blount, and Cheryl Mackowiak, describes information gained from a mineral study component of a four-year grazing study at NFREC Beef Unit, to measure monthly concentrations of selected minerals in forage during the late fall-winter-spring grazing season in north Florida. Published by the UF Department of Animal Science, August 2009.